2021
DOI: 10.12982/cmujns.2021.068
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Excellent ACE Inhibitor Agents from Scurrula atropurpure and Dendrophthoe pentandra for Anti-Hypertension

Abstract: The objective of this study was to investigate the bioactivity, toxicity, and interaction of the prepared bioactive compounds from Scurrula atropurpurea and Dendrophthoe pentandra with angiotensin-converting enzyme (ACE) macromolecule via an in-silico route. The bioactivity was investigated through Way2Drug PASS Online program. The drug-likeness property and human intestinal absorption of the bioactive compounds were evaluated through absorption, distribution, metabolism, and excretion (ADME) analysis. The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Additionally, similar results were also found in phytochemicals. An in silico approach revealed that quercitrin isolated from DP possessed a harmless LD 50 , but long-term use was not suggested ( Sjakoer et al, 2021 ). The total flavonoids of DP leaves growing on Polyalthia longifolia (Sonn.)…”
Section: Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, similar results were also found in phytochemicals. An in silico approach revealed that quercitrin isolated from DP possessed a harmless LD 50 , but long-term use was not suggested ( Sjakoer et al, 2021 ). The total flavonoids of DP leaves growing on Polyalthia longifolia (Sonn.)…”
Section: Toxicitymentioning
confidence: 99%
“…With the development of medical plants combined with modern technology, potential active molecules have been revealed in medicine made from two or more plants. For example, bioactive molecules including flavonol, kaempferol, casticin, quercetin, quercitrin, and isoquercitrin were yielded from DP and Scurrula atropurpurea (Blume) Danser via molecular-specific docking analysis, and found to possess suppressive effects on the angiotensin-converting enzyme responsible for hypertension ( Sjakoer et al, 2021 ). Quercetin, kaempferol, and aloe-emodin produced from DP and Cassia alata L. were able to inhibit the SARS coronavirus major peptidase and the 3-chymotrypsin-like cysteine protease 3 enzyme using a computational approach, suggesting their potential development as candidates against COVID-19 ( Ernawati et al, 2021 ).…”
Section: Applicationsmentioning
confidence: 99%